Values and challenges of participatory art in urban and community development: a 10-year systematic review - Ke, Zichen (Frontiers in Sociology, 2025)
Participatory art is increasingly recognised as a viable intervention initiative in engaging public participation for urban and community development, effectively addressing social challenges. This study selected 20 key articles published in the past 10 years from the Web of Science (WoS) and Scopus databases, covering diverse cultural and socio-political contexts. Through thematic analysis, it identified six core values, social empowerment and democratisation, multidimensional communication, enhanced community cohesion, local cultural identity, educational promotion, and economic benefits. Additionally, it highlights the four significant challenges, including political and commercial antagonism, social participation and acceptance, sustainability issues, and resource and funding problems. The findings provide practical guidance for policymakers, practitioners, and relevant stakeholders, helping to navigate complexities, maximise the benefits of this initiative, and address the identified challenges.